Case Report: Mammary Paget’s disease with multifocal microinvasive carcinoma and extensive lymph node metastasis: therapeutic challenges and insights from a case of stage pT1mic pN3c cM0 - Luo, YiFan; Liu, ZhiYu; Luo, Jing (Frontiers in Oncology, 2026)
BackgroundMammary Paget’s Disease (MPD) is a rare subtype of breast cancer, accounting for 1%-4% of all breast cancers. Controversy remains regarding whether sentinel lymph node biopsy (SLNB) is necessary for MPD patients undergoing breast-conserving surgery (BCS) when imaging studies fail to detect deep invasive carcinoma, and this controversy lacks support from specific case evidence.Case SummaryA patient presented with “recurrent left nipple fissure for 3 years and eczematous changes for 3 months.” Preoperative biopsy at another hospital confirmed MPD; imaging showed no deep mass. Postoperative pathology revealed left breast MPD associated with multifocal microinvasive carcinoma, accompanied by metastases to left axillary lymph nodes (6/8), left subclavian lymph nodes (2/3), and left supraclavicular lymph nodes (1/3). The pathological stage was pT1mic pN3c cM0. No recurrence was observed 6 months after adjuvant therapy with the TCbHP regimen plus capecitabine consolidation therapy.ConclusionAlthough no definite mass was identified on breast magnetic resonance imaging (MRI) in this case, SLNB and subsequent pathology confirmed extensive lymph node metastasis (pN3c). Omission of SLNB could have led to understaging and compromised treatment decision-making. This single case may suggest that SLNB holds significant staging value for MPD patients with no obvious breast mass on imaging. It provides hypothesis-generating, practical evidence for addressing this controversial clinical issue, warranting further investigation in larger cohorts.